Communication and media research during Covid-19 pandemic - Buyong, Mazni; Ahmad, Zeti Azreen (Communication and Media Centre (COMET), 2022)
COVID-19 disease caused by SARS-CoV2 virus has caused an unprecedented impact in almost every aspect of human life around the globe. By August 2022, there have been more than 500 million cumulative cases and the death toll has exceeded six million worldwide (WHO, 2022). The battle to fight the unseen virus came along with infodemic; “a massive amount of information that includes a mixture of true and false narratives” (Ahmad, Buyong & Souket, 2022, p. 87) that are hard to discern. This makes intervention efforts to contain the spread of the virus even more complicated. The ordeal in dealing with COVID-19 continues with the emergence of new variants which are believed to be more contagious, e.g., Delta, Alpha and Omicron. Scientists are working around the clock to learn how the virus mutates into different variants. At the same time, academics and researchers from all disciplines have shifted their focus to the implication of this severe public health crisis to socio-political conditions, economy, education, media, well-being and many other areas. Similarly, communication and media studies continue to cover the usual research topics such as media usage, media content, ethics, law, crisis management, types of media use, to name a few, but within the context of the COVID-19 pandemic. The unprecedented effect of COVID-19 serves as a wake-up call for hard sciences and social sciences researchers to work together to find the best alternatives for the population to continue with their life. In the meantime, countless efforts have been made to communicate about the disease using various forms of media. Numerous communication strategies have been used by the government and public health authorities to communicate about COVID-19 to all levels of stakeholders in society. A clear information about COVID-19 and its preventive measures would help to empower the population to protect themselves, their family and community from the fatal disease. Access to trustworthy information and ability to understand scientific information such as COVID-19 disease are fundamental in the midst of the infodemic. The proliferation of social media that carries diverse opinions and perspectives about the disease has been a constant challenge to COVID-19 intervention efforts. This article addresses how the pandemic shapes news and information in the media and the issue of trust. It will later delve on how COVID-19 affects research activities and some ethical concerns of conducting research online.